2019
DOI: 10.3390/ma12132142
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Comparative Effect of Sintering Methods and Sintering Additives on the Microstructure and Performance of Si3N4 Ceramic

Abstract: The Si3N4 ceramics were prepared in this study by gas pressure sintering (GPS) and spark plasma sintering (SPS) techniques, using 5 wt.% Yb2O3–2 wt.% Al2O3 and 5 wt.% CeO2–2 wt.% Al2O3 as sintering additives. Based on the difference in sintering methods and sintering additive systems, the relative density, phase composition, phase transition rate, microstructure, mechanical properties, and thermal conductivity were comparatively investigated and analyzed. SPS proved to be more efficient than GPS, producing hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Thus, it was confirmed that SPS is more efficient than a conventional technique like GPS, producing higher bending strength, hardness, and thermal conductivity of Si 3 N 4 ceramics with both additive systems. 97 Yu et al studied the effect of sintering temperature and additives on the relative density of Si 3 N 4 ceramic fabricated by SPS. They observed that with an increase in sintering temperature, relative densities of the samples increased from 76% to 99% due to the formation of the liquid phase which assisted phase transformation and rearrangement.…”
Section: Microstructure and Densification Behavior Of Si 3 N 4 In Spsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it was confirmed that SPS is more efficient than a conventional technique like GPS, producing higher bending strength, hardness, and thermal conductivity of Si 3 N 4 ceramics with both additive systems. 97 Yu et al studied the effect of sintering temperature and additives on the relative density of Si 3 N 4 ceramic fabricated by SPS. They observed that with an increase in sintering temperature, relative densities of the samples increased from 76% to 99% due to the formation of the liquid phase which assisted phase transformation and rearrangement.…”
Section: Microstructure and Densification Behavior Of Si 3 N 4 In Spsmentioning
confidence: 99%
“…All the prepared samples showed incomplete phase transformation and microstructure contained high aspect ratio b-Si 3 N 4 grains and intergranular glass. A maximum density of 3.16 g/cm 3 was obtained when SPS 97 was carried out at 1550 C. Figure 6 shows the displacement versus temperature plot during SPS for silicon nitride powders with fluoride and oxide additives. It can be seen from Figure 12, that MgF 2 shrinks at a lower temperature (1300 C) than MgO which shrinks at a higher temperature (1350 C).…”
Section: Microstructure and Densification Behavior Of Si 3 N 4 In Spsmentioning
confidence: 99%
See 1 more Smart Citation
“…Today the most sought-after researchers are focused on creating new nanomaterials by advanced spark plasma sintering (SPS) [37,39,[82][83][84]. The development and creation of new progressive nanocomposite materials based on ceramic-ceramic and metal-ceramic compositions strengthened with metal nanoparticles and carbides, carbon nanotubes and nanofibers, graphene and graphene oxide are popular due to improved physical and mechanical properties and chemical inertness.…”
Section: Production Of Nanoceramics By Advanced Spsmentioning
confidence: 99%
“…The artificially made metal and metalloid nitrides have been for sound reasons a focus of intensive research in recent years [ 1 ]. This is supported by the successful examples of such paramount applications of Group III nitrides as in efficient UV to blue range operating optoelectronic devices and white LEDs [ 2 ], by unmatched various ceramics/electronic applications for aluminium nitride AlN [ 3 , 4 ], boron nitride BN [ 5 ], silicon nitride Si 3 N 4 [ 6 , 7 ], and titanium nitride TiN [ 8 ] or by the extensively studied applications of broad bandgap semiconductor gallium nitride GaN [ 1 , 2 , 9 , 10 ]. In this regard, composites made of the nitrides offer various attractive capabilities by utilizing the synergy of coexisting electronic and mechanical/thermal properties.…”
Section: Introductionmentioning
confidence: 99%